Empty fruit bunch cellulose based sorbent for oil sorption in palm oil mill effluent - Noraisah Jahi,; Rizafizah Othaman,; Azwan Mat Lazim,; Suria Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aim of this study was to develope hydrophobic biodegradable cellulosic sorbent materials from empty fruit bunch (EFB) for oil sorption in palm oil mill effluent (POME). EFB cellulose was modified using acetic anhydride (AA) and the effect of ratio of EFB cellulose mass to AA volume (1:20, 1:30, 1:40, 1:50 g/mL) at 3 h reaction time with 5% (w/v) pyridine catalyst. The acetylation process was quantitatively determined using the weight percent gain (WPG) and modified EFB cellulose (1:40) showed the highest WPG (13.0%) compared to the other ratios. Fourier Transform Infrared (FTIR) spectrum shows that after the modification, the intensity of –OH peak at 3329 cm-1 decreased and the new peak at 1728 cm-1 of C=O ester emerged. This implied that acetylation process was successful when AA volume increased except for 1:50 ratio. Sample 1:40 also showed good hydrophobicity characteristic with the degree of hydrophobicity (DH) of 87.7%. X-ray diffraction (XRD) analysis shows that crystallinity index for 1:40 is the lowest which indicated that the sample become amorphous due to acetylation. The result is in agreement with scanning electron microscope (SEM) micrograph that shows the surface morphogy of EFB cellulose after the modification became rougher. Moreover, the modified EFB cellulose 1:40 was able to absorb oil from POME up to 98.5%. Thus, it is proven that cellulose from EFB can be modified to a certain ratio to make it an extremely promising natural source oil sorbent in treating POME.